Design and Verification of an Integrated Multi-task Testing Platform for FCV Powertrain System. (October 2018) - Tong, Zhang; Haiyu, Gao; Juexiao, Chen; Feng, Liu; Hua, Chai; Huicui, Chen
Abstract: With Fuel Cell Vehicle (FCV) enters into the beginning of production phase, it is an industry blank for comprehensive testing platform of development and productlization of FCV powertrain system and its key components. Distributed multi-task dynamic testing platform of FCV powertrain system is proposed in this paper, which can simulate the vehicle operation environment, road vibration adaptability and dynamic road resistance. Combined with the application of XiL(X-in-the-Loop) technology, it can realize the full top-down testing for FCV powertrain system, to solve the key problems of productlization verification for environment adaptability, road adaptability, durability and component consistency. Main controller is the operation core of the testing platform, the testing system architecture and functions were designed based on functional features and reliability. The verification process and test case were designed with XiL technology. Through the analysis of the test results, the effectiveness and the advanced features of the testing platform are demonstrated, and the design method for large-scale and multi-level test platform of FCV powertrain filed is verified as well.